Association of Interleukin-6–174G/C Polymorphism With Ischemic Stroke: An Updated Meta-Analysis - Chai, Jie; Cao, Xian-Ling; Lu, Feng (Frontiers in Neurology, 2022)
Background Numerous epidemiological studies have evaluated the association between the -174G/C(rs1800795) polymorphism in the promoter region of interleukin-6(IL-6) gene and the risk of ischemic stroke(IS) but failed to reach a consistent conclusion. The true relationship between -174G/C(rs1800795) polymorphism and IS is still controversial and unclear. Therefore, in this meta-analysis, we aimed to more precisely analyze the association between -174G/C(rs1800795) SNP of IL-6 gene with IS in a larger pooled population. Method A comprehensive literature search was performed in PubMed、Web of science and the Cochrane central register of controlled trials (up to 30 June 2021). A fixed-or random-effects model was used according to the heterogeneity among studies. The odds ratios (ORs) and 95% confidence intervals (CIs) were calculated in the models of allele comparison (G vs C), homozygote comparison (GG vs CC) and (GC VS CC), dominant (GG vs GC + CC), hyperdominant (GG+CC VS GC) and recessive (GG + GC vs CC) to estimate the strength of the associations. Results: Thirteen case–control studies in 35 articles with 5548 individuals were included in this meta-analysis. Overall, no significant associations between IL-6 -174G/C(rs1800795) and IS were identified from (G VS C:OR[95%CI]=0.99[0.81,1.21], P=0.91; GG+CC VS GC:0.97[0.85, 1.11], P=0.66; GG VS GC+CC: 1.01[0.81,1.25], P=0.94; GC VS CC: OR[95%CI]=1.01[0.68,1.50], P=0.96; GG VS CC: 0.93[0.57,1.51], P=0.76; GG+GC VS CC: 0.97[0.64,1.47], P=0.89). In subgroup analyses by ethnicity or HWE p value, there was a statistically significant association between IL-6 -174G/C(rs1800795) polymorphisms and IS in allele model (G vs C:LogOR[95%CI]=0.14[-0.16,0.45], P=0.00), homozygote model (GG vs CC:LogOR[95%CI]=0.18[-0.58, 0.95], P=0.00) and (GC VS CC:LogOR[95%CI]=0.20[-0.46,0.85], P=0.00), dominant model (GG vs GC + CC:OR[95%CI]=0.02[-0.72,0.77], P=0.00), and recessive model (GG + GC vs CC:OR [95%]=-0.17[(-0.86,0.52], P=0.00) of European and in dominant model (GG vs GC + CC:OR[95%CI]=-0.13[-0.51,0.24]) of Asian.No statistical significance was identified in both six model of HWE p≥0.2group (both P≥0.05). Conclusion: This meta-analysis showed no relationship between IL-6 -174G/C(rs1800795) polymorphism and IS, but subgroup analysis showed that relationship between IL-6 -174G/C(rs1800795) polymorphism and IS susceptibility varies significantly by race, and geography.